Characterization and engineering of plastic-degrading polyesterases jmPE13 and jmPE14 from Pseudomonas bacterium - Zhou, Xiaoli; Zhou, Xianmin; Xu, Zhiqiang; Zhang, Mingxia; Zhu, Honghui (Frontiers in Bioengineering and Biotechnology, 2024)
Polyester plastics are widely used in daily life, but also cause a large amount of waste. Degradation by microbial enzymes is the most promising way for the biobased upcycling of the wastes. However, there is still a shortage of high-performance enzymes, and more efficient polyester hydrolases need to be developed. Here we identified two polyester hydrolases, jmPE13 and jmPE14, from a previously isolated strain Pseudomonas sp. JM16B3. The proteins were recombinantly expressed and purified in E. coli, and their enzymatic properties were characterized. JmPE13 and jmPE14 showed hydrolytic activity towards polyethylene terephthalate (PET) and Poly (butylene adipate-co-terephthalate) (PBAT) at medium temperatures. The enzyme activity and stability of jmPE13 were further improved to 3- and 1.5-fold, respectively, by rational design. The results of our research can be helpful for further engineering of more efficient polyester plastic hydrolases and their industrial applications.